EORTHE: BUMI [BOOK ONE] - Astari - -; Budi Darma (Institute of Research and Community Outreach - Petra Christian University, 2014)
This creative project is a novel that is telling the story of a young man named, Rei, in his journey to find the truth about his late parents to help him find who he is, and a young princess called Aria in her quest, accompanied by Rei and their friends, in order to regain her right as the one and only successor to the throne of a Kingdom named Earendel. In this story, I decided to use quest and social criticism as the two main themes, while the sub-themes are quest for identity, quest for power, and for social criticism, it is change versus tradition. This to assist me in realizing my aim for writing this work which is to help raising more awareness towards our surroundings by promoting discovery process in the young adult world and social change. During their journey, the two major characters will see how some people is still having difficulty in accepting a change in their tradition from having men as the heads of the family to having a woman as one. The family here represents the patriarchal tradition or custom that most of families hold. As for the genre, I chose fantasy with the sub-genre epic fantasy and using the common epic fantasy properties, such as magic, supernatural creatures, the quest conducted by the two major characters, and also the existence of the good and the evil one.